2017
DOI: 10.1038/s41598-017-10590-w
|View full text |Cite
|
Sign up to set email alerts
|

Chloride Channels are Involved in the Development of Atrial Fibrillation – A Transcriptomic and proteomic Study

Abstract: AbstarctElectrical and structural remodeling processes are contributors to the self-perpetuating nature of atrial fibrillation (AF). However, their correlation has not been clarified. In this study, human atrial tissues from the patients with rheumatic mitral valve disease in either sinus rhythm or persistent AF were analyzed using a combined transcriptomic and proteomic approach. An up-regulation in chloride intracellular channel (CLIC) 1, 4, 5 and a rise in type IV collagen were revealed. Combined with the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 48 publications
2
23
0
Order By: Relevance
“…MiR-130b-3p was upregulated in RA samples in line with a previous study [31]. MiR-130b-3p is predicted to bind 15 of our down-regulated genes, amongst those there are CACNA2D2 and SLC7A11 which have been reported as down-regulated in AF transcriptomics studies [36,38,67]. CACNA2D2 is a subunit of the voltage-gated calcium channel that modulates the calcium signalling response in cardiomyocytes and induces arrhythmia when down-regulated [68].…”
Section: Plos Onesupporting
confidence: 82%
See 2 more Smart Citations
“…MiR-130b-3p was upregulated in RA samples in line with a previous study [31]. MiR-130b-3p is predicted to bind 15 of our down-regulated genes, amongst those there are CACNA2D2 and SLC7A11 which have been reported as down-regulated in AF transcriptomics studies [36,38,67]. CACNA2D2 is a subunit of the voltage-gated calcium channel that modulates the calcium signalling response in cardiomyocytes and induces arrhythmia when down-regulated [68].…”
Section: Plos Onesupporting
confidence: 82%
“…These inconsistencies might reflect 1) heterogeneity between tissue samples (location and collection method), 2) AF type and duration, 3) variation in patient cohorts (comorbidities, life-style, age, medication), and 4) the experimental technique selected to study transcript changes. In fact, our RNA-seq results overlap best with gene expression profiling studies from Jiang et al using similar tissue samples and experiments [38]. A continuous effort from experts to study larger cohorts and collect similar datasets will allow a combined analysis of multiple samples from AF patients and help on accurate selection of target genes and regulatory networks involving miRNAs.…”
Section: Plos Onesupporting
confidence: 52%
See 1 more Smart Citation
“…Downregulation of CLIC4 also reduced TGF-β1-induced expression of ECM components in primary fibroblasts [25]. In the development of atrial fibrillation, CLIC 1, 4, and 5 played an important role by interacting with collagen IV [26,27].…”
Section: Discussionmentioning
confidence: 96%
“…ClC-2 gene knockout inhibited TGF-β1-induced HConF collagen synthesis and collagen gel contraction. Multiple studies have shown that chloride channels are involved in collagen synthesis [24][25][26]. Qi et al [24] showed that the chloride channel blocker DIDS inhibited the collagen release of HFL1 fibroblasts.…”
Section: Discussionmentioning
confidence: 99%